Influence of carbon nanotubes on the thermal and mechanical properties of thermoplastic natural rubber (NR/LNR/LLDPE) composites / Hazwani Halim - Halim, Hazwani (2013)
In this research, the plastics (LLDPE) were mixed together with liquid natural rubber (LNR) as compatibilizer and natural rubber (NR) in a percentage of volume ratios 50:10:40 respectively to perform thermoplastic natural rubber (TPNR). This TPNR was reinforced with two types of MWNTs (MWNTs 1 and MWNTs 2). MWNTs 1 is untreated MWNTs (MWNTs without acid treatment) while MWNTs 2 is acid treated MWNTs. MWNTs has been choosen to be a reinforced material (filler) in this study because its exhibit unique mechanical, electronic and magnetic properties. Therefore, this may suggest the enhancement of composites properties as well as the application of it. This blend of composites was prepared via melt blending method using Haake 600 p internal mixer. Based on the optimum parameter, these nanocomposites were prepared at 140 °C temperature, 55 rpm of mixing speed and 13 minutes of processing time. The mechanical and thermal properties of this nanocomposites have been studied with respect to the various composition of MWNTs (2 wt%, 4 wt%, 6 wt% and 8 wt%) . Dynamic mechanical analysis (DMA) and morphological observation also conducted on the composites sample. It has been found that the tensile strength, Young’s modulus, and impact strength increase when the concentration of MWCNTs increase until 4 wt%. SEM micrographs have confirmed good dispersion of 2-4 wt% of MWNTs in TPNR. However the dispersion is low at higher content of MWNTs due to agglomeration of nanotubes inside the matrix. The thermal conductivity of the nanocomposites has increased with addition of MWNTs at various compositions.